2005
DOI: 10.1159/000083392
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Sarcoidosis

Abstract: The extrapulmonary presentation of sarcoidosis is a frequent occurrence – over 30% of cases when the observation is prospective – but early diagnosis may still be a challenge. A comparison between two different Italian series – (1) patients visiting the Milan Sarcoidosis Clinic of an Internal Medicine Department and (2) an Italian Register from many pneumology centers (RIPID) – has shown a different approach to the diagnosis because pneumologists are more likely to use transbronchial biopsy, while internists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Sarcoid lesions are most frequently present in the lung but can affect multiple organ systems, with 30% of the patients presenting with extra-pulmonary symptoms, with cardiac involvement carrying a significantly poorer outcome in terms of all-cause mortality [6][7][8][9]. Our study found that among both gender groups, females had a higher prevalence of sarcoidosis (65.2%) as compared to males (34.8%).…”
Section: Discussionmentioning
confidence: 52%
“…Sarcoid lesions are most frequently present in the lung but can affect multiple organ systems, with 30% of the patients presenting with extra-pulmonary symptoms, with cardiac involvement carrying a significantly poorer outcome in terms of all-cause mortality [6][7][8][9]. Our study found that among both gender groups, females had a higher prevalence of sarcoidosis (65.2%) as compared to males (34.8%).…”
Section: Discussionmentioning
confidence: 52%
“…Chest involvement in IBD is well known, and usually accompanies or follows the intestinal symptomatology. These manifestations include pulmonary function abnormalities, granulomatous inflammation with or without cavitation and drug-related lung disease [4,5,6,7,8,9]. The initial presentation of IBD by respiratory symptoms has not been described before to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…[123] It typically affects women in the age group from 20 to 60 years. It is diagnosed pathologically by the presence of noncaseating granulomas on biopsy of the lesion and presents in one or more of the following ways – pulmonary involvement in the form of hilar adenopathy or reticular shadows or extrapulmonary involvement in the form of eye/joint/skin/cardiac/central nervous system lesions.…”
Section: Discussionmentioning
confidence: 99%